2021
DOI: 10.1097/cce.0000000000000433
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Biological Sex on Sepsis Treatments in Animal Models: A Systematic Review and a Narrative Elaboration on Sex- and Gender-Dependent Differences in Sepsis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 153 publications
1
23
0
Order By: Relevance
“…For example, sex-based differences in gut microbiota composition have been shown to impact systemic immunity in diseases like diabetes 151,152 . In mice, sexual dimorphism is associated with differences in protection against sepsis, yet the mechanisms underlying this remain unexplored including a potential role for sex-based differences in the microbiota 153 . Lastly, our understanding of microbiota-immune interactions to date has been very bacteria-centric, and yet there is emerging data that other kingdoms of commensal microbes have a powerful impact on systemic immunity and host defense.…”
Section: Discussionmentioning
confidence: 99%
“…For example, sex-based differences in gut microbiota composition have been shown to impact systemic immunity in diseases like diabetes 151,152 . In mice, sexual dimorphism is associated with differences in protection against sepsis, yet the mechanisms underlying this remain unexplored including a potential role for sex-based differences in the microbiota 153 . Lastly, our understanding of microbiota-immune interactions to date has been very bacteria-centric, and yet there is emerging data that other kingdoms of commensal microbes have a powerful impact on systemic immunity and host defense.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, our results may help to better explain sex differences in postsepsis ICU survival given that females may have better survival compared with males. [8][9][10][11] These unique sex-related changes may be imparted on the host microbiota by the impact of sepsis and chronic stress. Such changes may lead to a chronic inflammatory state seen in PICS.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, one study demonstrated that, in patients younger than 90 years, women had significantly decreased 1-year mortality compared with males 10 . Regardless, it is clear that females and males respond differently to infection 8–10 . Future successful interventions for sepsis will need to use personalized/precision medical therapies, which will require a better understanding of the differences in host response due to severe infection.…”
mentioning
confidence: 99%
See 2 more Smart Citations